Case Report: Durable Clinical Response to Third-Line Pyrotinib After Resistance to Trastuzumab in a Gastric Cancer Patient - Wu, Junyi; Li, Lei; Qin, Jun; Yan, Zhengqing; Chen, Shiqing; Jin, Tao; Xu, Junming (Frontiers in Oncology, 2022)
Background Trastuzumab plus chemotherapy remains the standard first-line treatment strategy for HER2-positive gastric cancer (GC). Trastuzumab resistance, on the other hand, remains a significant issue. There are a few effective anti-HER2 agents for patients who develop resistance to trastuzumab. Case Presentation A 49-year-old female was diagnosed with stage IV GC with liver and lung metastasis in July 2017. She underwent gastrostomy, and the immunohistochemistry (IHC) result of postoperative tissue demonstrated HER2 (3+). She received first-line treatment of trastuzumab (440 mg), oxaliplatin (200 mg), and S-1 (40 mg). After treatment for 6 months, the patient achieved complete response (CR) with PFS up to 21 months. After progression, she subsequently received trastuzumab (440 mg) plus oxaliplatin (200 mg) as second-line treatment. However, the patient developed resistance to trastuzumab after 12 months of treatment. She started to receive third-line treatment of irinotecan (200 mg d1) and capecitabine (60 mg bid) plus pyrotinib (400 mg/day). After 2 months of treatment, the tumor is evaluated as partial response with PFS of 12 months. Conclusions We presented a patient with HER2-positive GC who benefited from the pyrotinib-based treatment after two lines of trastuzumab-based therapies failed. Further research is required to validate such conclusions.